Four‐year incidence of major adverse cardiovascular events in patients with atherosclerosis and atrial fibrillation. Issue 5 (27th February 2020) - Miao, Benjamin; Hernandez, Adrian V.; Roman, Yuani M.; Alberts, Mark J.; Coleman, Craig I.; Baker, William L.
Abstract: Background: There is a paucity of contemporary data assessing the implications of atrial fibrillation (AF) on major adverse cardiovascular events (MACE) in patients with or at high‐risk for atherosclerotic disease managed in routine practice. Hypothesis: We sought to evaluate the 4‐year incidence of MACE in patients with or at risk of atherosclerotic disease in the presence of AF. Methods: Using US MarketScan data, we identified AF patients ≥45 years old with billing codes indicating established coronary artery disease, cerebrovascular disease, or peripheral artery disease or the presence of ≥3 risk factors for atherosclerotic disease from January 1, 2013 to December 31, 2013 with a minimum of 4‐years of available follow‐up. We calculated the 4‐year incidence of MACE (cardiovascular death or hospitalization with a primary billing code for myocardial infarction or ischemic stroke). Patients were further stratified by CHA2 DS2 ‐VASc score and oral anticoagulation (OAC) use at baseline. Results: We identified 625, 951 patients with 4‐years of follow‐up, of which 77, 752 (12.4%) had comorbid AF. The median (25%, 75% range) CHA2 DS2 ‐VASc score was 4 (3, 5) and 64% of patients received an OAC at baseline. The incidence of MACE increased as CHA2 DS2 ‐VASc scores increased ( P ‐interaction<.0001 for all). AF patients receiving an OAC were less likely to experience MACE (8.9% vs 11.6%, P < .0001) including ischemic stroke (5.4% vs 6.7%, P < .0001). Conclusion: Comorbid AF carries a substantial risk of MACE in patients with or at risk of atherosclerotic disease. MACE risk increases with higher CHA2 DS2 ‐VASc scores and is more likely in patients without OAC.